2005
DOI: 10.1016/j.femsim.2004.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a peroxiredoxin–glutaredoxin byHaemophilus influenzaein biofilms and during human respiratory tract infection

Abstract: Evidence is mounting that nontypeable Haemophilus influenzae grows as a biofilm in the middle ear of children with otitis media and the airways of adults with chronic obstructive pulmonary disease. To begin to assess antigens expressed by H. influenzae in biofilms, cell envelopes of bacteria grown as a biofilm were compared to those grown planktonically. A approximately 30kDa peroxiredoxin-glutaredoxin was present in greater abundance during growth in biofilms. Mutants deficient in expression of peroxiredoxin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 43 publications
4
52
0
Order By: Relevance
“…While previous work showed that neither pdgX nor htkE encodes a virulence factor in the context of systemic infection by encapsulated H. influenzae (30,31), our work in this study clearly demonstrates a role for this factor in the persistence of nontypeable H. influenzae during localized infections. These findings are consistent with prior work showing that expression of pdgX is increased in biofilm expression and during chronic bronchitis infections (5).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While previous work showed that neither pdgX nor htkE encodes a virulence factor in the context of systemic infection by encapsulated H. influenzae (30,31), our work in this study clearly demonstrates a role for this factor in the persistence of nontypeable H. influenzae during localized infections. These findings are consistent with prior work showing that expression of pdgX is increased in biofilm expression and during chronic bronchitis infections (5).…”
Section: Discussionsupporting
confidence: 93%
“…In patients with mucociliary clearance deficits, NTHI can also cause opportunistic infections; these include airway infections in patients with chronic obstructive pulmonary disease (COPD) (2) and otitis media infections in children (3). These infections are often chronic and recurrent in nature, and it is now well established that the persistent NTHI populations reside within biofilm communities on the airway surface (4)(5)(6). NTHI persists in the chinchilla middle ear even in the face of immune effectors that contribute to the biofilm structure, such as neutrophils and neutrophil extracellular traps (NETs) (7).…”
mentioning
confidence: 99%
“…In the latter regard, extracellular DNA has been shown to act as a cell-to-cell interconnecting component in biofilms produced by P. aeruginosa and S. pneumoniae (2,23,27,31). However, whereas LOS in a specific linkage group as well as several outer membrane proteins, surface proteins, and adhesins (15,16,19,25,36,40) have been identified in NTHIproduced biofilms, the presence of dsDNA in these matrices has, to the best of our knowledge, never been described. In fact, to date, studies characterizing the presence of DNA in any biofilm matrix have focused on those formed in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…NTHI is a leading cause of otitis media with effusion (2), acute otitis media (1), chronic sinusitis (20), and pulmonary infections associated with chronic obstructive pulmonary disease (31). For many of these infections, NTHI bacteria persist within dense biofilm communities that are thought to provide resistance to host clearance (12,25,29). NTHI biofilms contain variants expressing lipooligosaccharides (LOS) that contain phosphorylcholine (PCho) and sialic acid (NeuAc) (10,19,36,41).…”
mentioning
confidence: 99%